2022
DOI: 10.1111/1751-7915.14110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional role of Domain I for the insecticidal activity of the Vip3Aa protein from Bacillus thuringiensis

Abstract: Vip3 proteins are produced by Bacillus thuringiensis and are toxic against lepidopterans, reason why the vip3Aa gene has been introduced into cotton and corn to control agricultural pests. Recently, the structure of Vip3 proteins has been determined and consists of a tetramer where each monomer is composed of five structural domains. The transition from protoxin to the trypsin‐activated form involves a major conformational change of the N‐terminal Domain I, which is remodelled into a tetrameric coiled‐coil str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…It is noteworthy that, although Cry and Vip3 proteins have different primary sequences, the structural domains of Vip3 toxins resemble the first three domains reported for Cry toxins. Aside from the common shape-folded domains, it has been widely accepted that β-stranded domains of Vip3 and Cry toxins are involved in receptor binding ( 75 ), whereas the helical domains play a critical role in oligomerization and membrane insertion ( 76 ). The α-helical domain I of Vip3 is not present in Cry toxins, and Vip3 has two β-sandwich structural domains (domains IV and V) that share structural similarities with the β-sandwich domain III of Cry toxins.…”
Section: Structural Changes Of Vip3 Toxins During Pore Formationmentioning
confidence: 99%
“…It is noteworthy that, although Cry and Vip3 proteins have different primary sequences, the structural domains of Vip3 toxins resemble the first three domains reported for Cry toxins. Aside from the common shape-folded domains, it has been widely accepted that β-stranded domains of Vip3 and Cry toxins are involved in receptor binding ( 75 ), whereas the helical domains play a critical role in oligomerization and membrane insertion ( 76 ). The α-helical domain I of Vip3 is not present in Cry toxins, and Vip3 has two β-sandwich structural domains (domains IV and V) that share structural similarities with the β-sandwich domain III of Cry toxins.…”
Section: Structural Changes Of Vip3 Toxins During Pore Formationmentioning
confidence: 99%
“…Cryo-EM studies have revealed the tetrameric structure of Vip3Aa protoxin and trypsin-activated toxin, with each monomer being composed of five domains [ 14 ]. Domain I, containing four α-helices, plays a crucial role in both oligomerization and insecticidal activity [ 17 ]. This domain undergoes a conformational change during proteolytic activation, where helices α1 to α3 unfold and form a new N-terminal coiled-coil interacting with membranes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic digestion analysis also confirmed that domain I is a 19 kDa fragment of Vip3 toxins [ 11 ]. The crucial role of helix α1 in domain I has been shown for the insecticidal activity of the Vip3Aa toxin [ 17 ]. Domain II is composed of five α-helices, being the core of the tetramer that stabilizes the oligomeric structure [ 14 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the insect midgut, tetrameric Vip3 protoxins are cleaved and activated by proteases such as trypsin. The activated toxins then bind potential receptors on the surfaces of the epithelial cells lining the midgut, form pores on the cell membranes, and cause cell death 10,17–20 . Studies on the functional mechanisms of Vip3 have facilitated its application in agriculture and advanced research on Sips 21–25 …”
Section: Introductionmentioning
confidence: 99%
“…The activated toxins then bind potential receptors on the surfaces of the epithelial cells lining the midgut, form pores on the cell membranes, and cause cell death. 10,[17][18][19][20] Studies on the functional mechanisms of Vip3 have facilitated its application in agriculture and advanced research on Sips. [21][22][23][24][25] Far less research has been conducted on Sips than on Cry and Vip3 toxins.…”
Section: Introductionmentioning
confidence: 99%